Book Review: Alcaraz, E., & Hughes, B. (2002). Legal Translation Explained. Manchester: St. Jerome Publishing. ISBN: 978-1-900650-57-2 - Almjlad, Sultan (Comparative Legilinguistics, 2025)
This review critically examines Legal Translation Explained (2002) by Enrique Alcaraz and Brian Hughes, a seminal work in the field of legal translation. The book offers a comprehensive integration of linguistic, legal, and translational perspectives, positioning the translator as a bicultural and bilingual mediator. Structured around genre-based and functionalist principles, the book explores legal language, translation equivalence, legal systems, and text typologies, while providing practical strategies for addressing terminological, stylistic, and procedural challenges. This review analyzes the book’s contribution to legal translation pedagogy and theory, highlighting its alignment with key frameworks such as Skopos theory, functional equivalence, and intercultural legal communication. The enduring relevance of the book is also evaluated in light of recent developments in legal translation studies. Ultimately, the review argues that Alcaraz and Hughes’s work remains an indispensable resource for both scholars and practitioners seeking to navigate the complexities of legal-linguistic mediation.